Agro Morphological Trait and Yield Component Evaluation of Malt Barley (Hordeum Distichon L.) Varieties Response to the Rate of Fertilizer in Habro Woreda West Hararghe Zone, Oromia, Ethiopia - Shambel Kebede; Bekele Kindie, (Indian Journal of Advanced Botany (IJAB), 2024)
The study assessed the effects of NPSB Fertilizer Rate on Yield and morphological traits of Malt barley Varieties. The experiment used a Randomized Complete Block Design with three varieties and five levels of fertilizer rates. The effects of NPSB fertilizer rate and varieties were highly significant on all yield components; phenology and morphological traits. The highest number of kernels per spike (29.5), above ground biomass (12.0 tha-1), and straw yield (6.4 tha-1) were obtained from 200kg NPSB ha-1 , while highest the thousand grain weights (48.2g) were obtained from 150kg NPSB ha-1. The interaction effects of varieties and fertilizer rates were significant at p<0.05 on grain yield (5653.3) from the Traveller variety at 150 kg NPSB ha-1 fertilizer rates. The analysis of variance showed that the interaction effects of varieties and fertilizer rates were significant at p<0.05 on Hectoliter (69.133) from the Traveller variety at 150 kg NPSB ha-1 fertilizer rates. Finally, from the above result, it can be concluded that using 150 kg ha-1 NPSB fertilizer with Traveller variety can be recommended for malt barley production in the study area.